Transient liquid phase spark plasma sintering of B4C-based ceramics using Ti-Al intermetallics as sintering aid. Issue 10 (August 2016) - Ji, Wei; Todd, Richard I.; Wang, Weimin; Wang, Hao; Zhang, Jinyong; Fu, Zhengyi
Abstract: Fully-dense B4 C-based ceramics were fabricated using Ti-Al intermetallics as sintering aid by Spark Plasma Sintering at a low temperature of 1700 °C whilst applying 32 MPa uniaxial pressure. The influence of the intermetallic additions on the phase composition, morphology and mechanical properties of the ceramics were investigated. The intermetallics flowed and react with B4 C to form a three-phase composite containing B4 C, TiB2 and Al4 C3 during the transient liquid phase sintering process. The TiB2 and Al4 C3 particles were located on the boundaries between B4 C grains and effectively inhibited the growth of B4 C, which improved the mechanical properties. Good bonding between B4 C and the phases formed was confirmed by TEM analysis. The specimens with 5 wt.% Ti-Al provide an attractive combination of homogeneous morphology and excellent mechanical properties, including a Vickers hardness of 33.5 ± 0.4 GPa, a flexural strength of 506 ± 16 MPa and a fracture toughness of 5.5 ± 0.1 MPa m 0.5 .